Cervical prolapse during labor: A case report - Adugnaw Bogale Worku; Molla Asnake Kebede; Abebe Agegn Wudineh; Adefris Getachew Techane; Mekuanint Dessie Lakew; Chuchu Arega Zeleke (Case Reports in Women's Health)
Uterine prolapse during pregnancy is rare, occurring in approximately 1 in 10,000 to 15,000 deliveries. It presents significant risks to both maternal and fetal health, and the optimal delivery method depends on the severity of prolapse, labor progression, and the well-being of both mother and baby.A 25-year-old woman presented at 38 weeks and 4 days of gestation with vaginal mass protrusion and pain on pushing down. Examination revealed an irreducible cervical prolapse with swelling during the early stage of labor. Fetal ultrasound confirmed a normal head-down position and adequate amniotic fluid. Due to persistent fetal tachycardia, an emergency cesarean section was performed, resulting in the delivery of a healthy 3000 g male infant. Postoperatively, the mother was placed in the Trendelenburg position, which led to the spontaneous resolution of the prolapse by the third postpartum day. At the six-week follow-up, the uterine prolapse had completely resolved.This case emphasizes the importance of individualized management and timely intervention. Postpartum uterine prolapse often resolves spontaneously with conservative care. A multidisciplinary approach is crucial for optimizing maternal and fetal outcomes, especially in resource-limited settings.